Acara Adat Joget Kidah-Kidahan di Desa Sugihan Kabupaten Muara Enim - Ria, Intan; Nurdin, Nurdin; Siswanto, Silo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The Kidah-kidah dance traditional event is only carried out when a boy is going to performcircumcision, the Kidah-kidahan dance custom is an event aimed at Thanksgiving for boys who willcarry out the circumcision, this traditional event is also often called the little fiancé. but when smallchildren are called to start dancing, they will be called as Pence Dance, which means in pairs. Theobject of this research is the form of presentation of the traditional dance of kidah-kidahan. Thelocation of this research was carried out in Sugihan Village, Muara Enim Regency. In this study, the formulation of the problem is how the traditional dance of kidah-kidahan in Sugihan village, Muara Enim district, so after knowing the problem formulation in this study, it can be seen that the purpose of the research was to describe the form of presentation of kidah-kidahan dance in Sugihan village. The method used by the researcher is a qualitative descriptive method using Observation, Interview and Documentation Data Collection Techniques. The data analysis technique carried out by the researcher is that the researcher will see and examine the form of presentation of kidah-kidahan dances and the socio-cultural function in the Sugihan village community. In order for this research to be more accurate when it is being read, the researcher goes directly to the field and makes observations on the object being studied by means of interviews. The results of this study are that thekidah-kidahan dance has seven stages of activity and six forms of presentation and there are alsotwo functions, namely social functions and cultural functions.